Desain UlangTata Letak Pabrik Dengan Metode Systematic Layout Planning (SLP) Di Plant Welding Shop PT. Sanggar Sarana Baja - Putra Ivannah Hakim; Hadhimas Dwi Haryono; Doddy Suanggana (LPPM Politeknik LP3I Medan, 2021)
PT. Sanggar Sarana Baja is a company engaged in the manufacturing process, design, steel fabrication, service, product refurbishing and remanufacturing. The problem at the Plant Welding Shop of PT. Sanggar Sarana Baja is a machine layout that is not organized according to the production flow, which causes the distance between machines that should be close together quite far. This study uses the Systematic Layout Planning (SLP) method which is expected to get the results of a factory layout design that can reduce material handling distances and reduce material handling costs. After processing the data, the proposed layout design 2 is obtained with a displacement moment of 4,527 m / year, while in its initial condition it is 9,355 m / year. The amount of material handling costs was Rp. 5,840,559 / year, while in the initial condition it was Rp. 12,069,457.38 and the savings obtained were 51.61%. Based on the calculations made, the proposed layout design 2 is obtained which can minimize the distance and material handling costs.